Correlation between Nicotine Dependence and Cardiorespiratory Fitness within the Wellness Matrix Framework among University Students - Muhammad Ikhsan Ghaifazzari Ghafar; Ronny Lesmana; Setiawan Setiawan (Faculty of Medicine Universitas Padjadjaran, 2026)
Background: The increasing use of tobacco and electronic nicotine delivery systems (ENDS) among youth represents a significant public health concern. In Indonesia, nicotine use among university students may contribute to long-term health risks. This study evaluated the correlation between nicotine dependence, measured using the Hooked-on Nicotine Checklist (HONC), and cardiorespiratory fitness assessed through maximal oxygen uptake (VO₂max) within the Wellness Matrix Framework.Methods: A cross-sectional study was conducted among 40 male undergraduate students aged 18–24 years at Universitas Padjadjaran who actively used cigarettes, e-cigarettes, or vape products. Participants were selected using purposive sampling. Nicotine dependence was assessed using a modified HONC questionnaire, whereas VO₂max was estimated using the YMCA 3-Minute Step Test. Descriptive statistics, the Shapiro-Wilk tests, and Pearson correlations analysis were applied (α=0.10).Results: Participants showed moderate nicotine dependence (mean HONC score: 5.6 ± 2.37) and moderate fitness (mean VO₂max: 44.31±3.86 mL/kg/min). A weak inverse correlation was found between HONC scores and VO₂Max (r=-0.275, p=0.085). Body mass index showed a strong negative correlation with VO₂max (r=-0.824, p<0.001). Subgroup analysis showed consistent negative trends between nicotine dependence and VO₂max across single, dual, and triple product users. Duration of nicotine use showed negligible correlation with VO₂max (r=0.041, p=0.802). Conclusion: Higher nicotine dependence is associated with lower cardiorespiratory fitness and affects multiple wellness dimensions. These findings underscore the importance of holistic interventions targeting physical and psychosocial wellness among young adults.